PENGEMBANGAN MEDIA AJAR VISUAL “SAMBUNG PIPA” TERHADAP SISWA AUTISM SPECTRUM DISORDER (ASD) PADA PEMBELAJARAN TEMATIK KELAS 1 SEKOLAH DASAR - Annifa Salja; Muhammad Husni; Abdul Aziz (PGSD UNIKA SANTU PAULUS RUTENG, 2022)
Development of Visual Teaching Media “Connecting Pipes” to Autism Spectrum Disorder (ASD) Students in Class 1 Thematic Learning at MI Hamzanwadi No. 1 Pancor Academic Year 2021/2022, Proposal, Primary School Teacher Education Study Program (PGSD) Faculty of Education (FIP) Hamzanwadi University. This research was conducted with the aim of developing a visual teaching media “Connect Pipes” to Autism Spectrum Disorder (ASD) students in grade 1 thematic learning using the Borg and Gall research design which consists of 10 steps and then simplified into 7 steps, namely: (1) doing needs analysis, (2) planning, (3) initial product development, (4) limited testing, (5) revision of product test results, (6) main product test, (final product revision). This research was conducted on an autistic student in grade 1 who experienced barriers to communication, behavior and interaction. The research instrument used a material expert validation sheet, a media expert validation sheet and the responses of teachers and school principals. The results of the material expert validation test got a score of 97 in the range of scores X> 83.94 with the